Spontaneous brain and arachnoid herniation into the dural venous sinuses: a rare anatomic variation or clinical entity? - Hakija Bečulić; Rasim Skomorac; Aldin Jusić; Melica Imamović; Fahrudin Alić; Anes Mašović; Alma Mekić Abazović; Alma Efendić; Eldin Burazerović; Benjamin Halilović (Medicinski glasnik, 2017)
Aim: To investigate the presence, type and distribution of spontaneous brain and arachnoid herniation into the dural venous sinuses as well as a clinical significance of these herniations. Methods: This retrospective-prospective, non-randomised anatomical and clinical study included 990 patients who were referred to Magnetic Resonance Imaging at the Department of Radiology of the Cantonal Hospital in Zenica in the period from January to December 2016. The T1 and T2 sequences in axial, sagittal, and coronary section were used for brain or arachnoid herniation analysis. In all patients with intra-sinusal herniation health records were analysed and symptoms and reasons to refer for MRI examination were evaluated. Results: In 26 (2.6%) patients (19 females; 73.08%) the arachnoid or brain herniation was found. Average age of patients was 40.269±16.496 years. Arachnoid herniation was presented in 15 (57.69%) and brain herniation in 11 (42.31%) patients. Statistical significance in relation to type of herniation was not found (p=11.070). Statistical significance between the symptoms and localisation of herniation (except for nausea and vomiting and posterior fossa herniations) (p=0.05) as well us between symptoms and type of herniation was not found (p>0.05). Conclusion: The results suggest that there is a possibility of interconnection between arachnoid or/and brain herniations and some clinical symptoms such as nausea and vomiting.
Keywords: dural thinning; sinus abnormality; clinical significance